2002
DOI: 10.1002/art.10787
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture patients are not treated for osteoporosis: A call to action

Abstract: Objective. To determine whether hip fracture patients, a group at very high risk for additional fragility fractures, are being evaluated and treated effectively for osteoporosis. Methods. Clinical and bone densitometry (dual x-ray absorptiometry [DXA]) records were reviewed in hip fracture patients at 4 Midwestern US health systems to determine the frequency of DXA use, calcium and vitamin D supplementation, and antiresorptive drug treatment. Results. DXA was performed at the 4 study sites in only 12%, 12%, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 24 publications
4
73
0
4
Order By: Relevance
“…We began our improvement project by studying osteoporosis care in hip fracture patients because they have a high risk of additional fractures and were believed to be a small accessible subpopulation. A retrospective baseline study indicated that only 5% of 1999 hip fracture patients were referred for DXA or treated with an antiresorptive drug either before or after their fracture (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We began our improvement project by studying osteoporosis care in hip fracture patients because they have a high risk of additional fractures and were believed to be a small accessible subpopulation. A retrospective baseline study indicated that only 5% of 1999 hip fracture patients were referred for DXA or treated with an antiresorptive drug either before or after their fracture (8).…”
Section: Resultsmentioning
confidence: 99%
“…In our own health system (University of Wisconsin Medical Foundation [UW]), only 5% of patients who sustained a hip fracture in 1999 were provided DXA and bisphosphonate treatment, either before or after their fracture, and few patients were being referred for DXA because of other fragility fractures (8). In 2000, we began an improvement project to address this deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For patients in whom the baseline serum 25-hydroxyvitamin D level was 40 ng per milliliter or less, a loading dose of 50,000 to 60,000 IU of vitamin D was administered at the time the trial regimen was started. All patients received daily calcium (500 to 1000 mg) and vitamin D 3 or D 2 (600 to 800 IU).…”
Section: Patientsmentioning
confidence: 99%
“…1,2 Even after a fracture, fewer than 25% of patients receive pharmacologic treatment for osteoporosis. [3][4][5] After the discovery that sclerostin deficiency causes rare genetic conditions that are characterized by high bone mass and resistance to fracture, 6,7 sclerostin became a therapeutic target for the treatment of osteoporosis. Sclerostin, a negative regulator of bone formation that is secreted by osteocytes, 8 inhibits Wnt signaling, down-regulating this stimulus for osteoblast development and function.…”
mentioning
confidence: 99%
“…For example, Harrington et al 16 reported that across several health systems in the U.S. only 14% of hip fracture patients were prescribed vitamin D. A challenge in the diagnosis and management of vitamin D deficiency in this population is the expense and lack of local availability of high-quality vitamin D assays, many of which do not accurately measure levels of 25 hydroxyergocalciferol (25(OH)D2), or vitamin D2 received from dietary sources and supplements.…”
Section: Introductionmentioning
confidence: 99%